El Excentrico, 1958-06-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
June 5, 1958 [5 de junio de 1958]. Ano 8, No 19. Cover contains a group photo of Club Volante's Beauty Contest contestants, in swim attire. Two of them are holding up trophies, including Alice Coca, who was the 1st place winner. The headline reads, "Miss Alice Coca winner of Club Volante's Beauty Contest."